MENINGKATKAN HASIL BELAJAR SISWA KELAS IV SD MELALUI PENERAPAN MODEL PEMBELAJARAN TEAMS GAMES TOURNAMENT BERBANTUAN MEDIA MONOGAYA - Dewi Aisah; Erik Aditia Ismaya; Ahmad Bakhruddin (STKIP Subang, 2023)
The purpose of this study was to improve student learning outcomes in science learning by applying the Teams Games Tournament learning model assisted by MONOGAYA media for fourth grade students at SD N 1 Pelemkerep in May 2023 with material on Indonesian cultural diversity. The research method used in this study was classroom action research conducted in two cycles, each cycle consisting of four stages, namely planning, implementing, observing, and reflecting. The subjects in this study were the fourth grade students of SD N 1 Pelemkerep, which consisted of 15 students consisting of 5 male students and 10 female students. Data collection techniques in this study include interviews, observation, tests, and documentation. Student learning outcomes in the domain of cycle I skills obtained an average of 70% and increased to 82% in cycle II. Student learning outcomes in the domain of attitudes in cycle I obtained an average of 67% and in cycle II it increased to 73%. Based on these results it can be concluded that the application of the Teams Games Tournament learning model assisted by MONOGAYA media can improve and student science learning outcomes.